2011
DOI: 10.1371/journal.pone.0018474
|View full text |Cite
|
Sign up to set email alerts
|

Weight Variation over Time and Its Association with Tuberculosis Treatment Outcome: A Longitudinal Analysis

Abstract: ObjectiveWeight variation during therapy has been described as a useful marker to predict TB treatment outcome. No previous study has used longitudinal analysis to corroborate this finding. The goal of this study was to evaluate change and trends of patients' bodyweight over time depending on TB treatment outcome.Methods and FindingsA retrospective cohort study with all TB cases diagnosed from 2000 to 2006 was carried out. Information from 5 public tuberculosis treatment facilities at Pampas de San Juan de Mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 14 publications
(26 reference statements)
5
49
2
5
Order By: Relevance
“…[12,8,3,17] In our study 46.13% (173/375) female patients were registered, while 30.49%, 32.40% and 37.60% female patients were registered respectively at Nagpur, Delhi and Aurangabad. [8,3,17] In present study, higher weight gain (96.30%), higher successful treatment (98.18%), lower default rate (1.81%) and lower weight loss (1.85%) observed in age group of 0 -14 years, whereas lower weight gain (93.3%), lower successful treatment (65.21%), higher default rate (14.13%), higher death rate (13.04%) and higher weight loss (5.00%) in age above 45 years.…”
Section: Discussionmentioning
confidence: 66%
“…[12,8,3,17] In our study 46.13% (173/375) female patients were registered, while 30.49%, 32.40% and 37.60% female patients were registered respectively at Nagpur, Delhi and Aurangabad. [8,3,17] In present study, higher weight gain (96.30%), higher successful treatment (98.18%), lower default rate (1.81%) and lower weight loss (1.85%) observed in age group of 0 -14 years, whereas lower weight gain (93.3%), lower successful treatment (65.21%), higher default rate (14.13%), higher death rate (13.04%) and higher weight loss (5.00%) in age above 45 years.…”
Section: Discussionmentioning
confidence: 66%
“…[20] Previous work shows that weight and nutritional status are important parameters to predict the treatment outcome and survival among the patients and those losing weight in the 1 st month of treatment should be observed closely. [21][22][23] There are a few limitations to this study. This is a crosssectional study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have showed that patient's body weight is associated with treatment outcome [10][11][12]. However, some authors put forth that weight gain during antitubercular therapy appeared to be an unreliable indicator of overall treatment response [13].…”
Section: Discussionmentioning
confidence: 99%